The Wild Vulnerability of Paul B. Preciado in "Dysphoria Mundi": An example of autotheory as a factual narrative - Alonso Prieto, Javier (Tropelías: Review of Literary Theory and Comparative Literature, 2025)
Autotheory as a genre serves to encompass all artistic productions (not only literary) that overcome the friction between theory and art through self-representation. This line has a strong presence in postfeminist thought and manifests a revitalization of philosophy, art, and activism from a provocative and reivindicative autotheoretical approach. As a literary genre, it is defined and expanded in the 21st century, but it has illustrious precedents in writings framed in the theoretical paradigm shift of the second half of the 20th century.Dysphoria Mundi is a fragmentary book that partakes in philosophy and personal diary. Preciado criticizes traditional identity politics and proposes that gender dysphoria is not a mental illness, but a political and aesthetic inadequacy. He suggests a new form of subjectivation that transcends binary categories, advocating for a new language and a revolution in progress.
Keywords: autotheory; politic literature; biopoetics; trans; rhetoric